(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2023)
The article considers and analyzes the influence of sowing dates and rates, doses of mineral fertilizers on plant height, the length of ears and the number of spikelets per spike of winter rye varieties grown in light gray soils of Kashkadarya region.